DETERMINAN PERTUMBUHAN EKONOMI DAN TINGKAT KEMISKINAN DI KABUPATEN BULELENG - Putu Agung Krisna Dwipayana Putra; I Nyoman Mahaendra Yasa (Universitas Udayana, 2024)
This study aims to analyze the influence of the quality of human resources, UMK, and investment on economic growth and poverty levels in Buleleng Regency. The research location is in Buleleng Regency with secondary data obtained from the Central Bureau of Statistics (BPS). The number of observations in this study is 15 observations in the 2008-2022 timeframe using time series data. The data analysis technique used in this research is descriptive analysis and path analysis. The results of the research show that 1) the quality of human resources, district minimum wages (UMK), and investment have a positive and significant effect on economic growth; 2) The quality of human resources and investment has a negative and significant effect, the district minimum wage (UMK) has a negative and insignificant effect, while economic growth has no negative and significant effect on the poverty rate; 3) The quality of human resources, the District Minimum Wage (UMK), has an indirect effect, while investment does not indirectly affect the poverty rate through economic growth in Buleleng Regency. Keywords : human resources quality, district minimum wage (UMK), investment, economic growth, poverty rate